HUBUNGAN KONGRUENSI KARIER ANTARA REMAJA DAN ORANGTUA DENGAN PERENCANAAN KARIER PADA ANAK NELAYAN DI KAMPUNG NELAYAN KOTA TEGAL - Rani Kusuma; Annastasia Ediati (Faculty of Psychology, Diponegoro University, 2018)
Tegal City is located in the Central Java Province, precisely located in the North Coast area so that the majority of the population to work as a fisherman. People who work as fishermen not only from adulthood but also many adolescent who worked as a fisherman. This study aims to determine the relationship of adolescent-parent career congruence with career planning on fisherman’s son in Fisherman Village of Tegal City. The population of this study is the fisherman’s son age 12 – 15 years old who lives in Tegal City which amounts 110 people. The sample was taken by purposive random sampling technique with 68 children. The measure is used Adolescent-Parent Career Congruence Scale (9 aitem α = 0,760) and Career Planning Scale (21 aitem; α = 0,916). Pearson Product Moment correlation results known (r = 0.726; p <0.001) showed a positive and significant correlation between adolescent-parent career congruence with career planning on fisherman’s son in Fisherman Village of Tegal City. Parents are expected to be more active in providing support in the form of spirit, direction, and feedback about their future career planning so that their childcare plans are more mature.